Pengembangan Lembar Kerja Peserta Didik (LKPD) Elektronik Berbasis Masalah pada Materi Larutan Asam dan Basa - Danial, Muhammad; Rano, Felisitas Yanti; Herawati, Netti (Program Pasca Sarjana UNM, 2022)
This study is a development research that aims to develop problem-based e-LKPD on acid and base solutions which is valid, practical, and effective to be used to improve learning outcomes. The development model used in this study referred to the 4-D development model, which consisted of the defining stage, the design stage, the development stage, and the dissemination stage. The one developed was a problem-based electronic student’s worksheet (LKPD). The problem-based e-LKPD developed was then validated by two experts. After validation, a trial was conducted at SMKN 9 Jeneponto in grade X TKJ with a total of 22 students. The results show that the resulting e-LKPD is valid with an average validity value of 3.40 with valid criteria. The practicality test includes: (1) analysis of the teacher's response, the teacher gave a very positive response with an average value of 3.75 which means it is practical and not revised, (2) analysis of students’ responses, students gave a positive response with a percentage of 81.80 very responsive. This problem-based E-LKPD also meets the effectiveness criteria with learning outcomes meeting the effective criteria where the N-Gain of 0.64 increases in learning outcomes which is in moderate category, the percentage of completeness is 81.82% which is in good category.